The protection of the environment in maritime management - Jabłoński, Maciej (Studia Ecologiae et Bioethicae, 2012)
The maritime economy is a field that has a significant impact on the functioning of the entire global economy. Therefore, it is important to comply with high standards of environmental protection, which must be implemented in an effective way by public administrative bodies. Only in this way can the principle of the responsibility for entering into marine environment pollutants be implemented.